Efeitos da perda de peso sobre o metabolismo ósseo de pacientes submetidos à cirurgia bariátrica de Bypass Gástrico em Y de Roux: efeitos da cirurgia bariátrica sobre o metabolismo - Biagioni, Maria Fernanda Giovanetti [UNESP] (2015)
Introduction: despite the success at weight loss and control of comorbidities, bariatric surgeries such as gastric bypass Roux-Y (RYGB), promote changes in hormone metabolism and adipose tissue, which may be associated with increased remodeling and bone loss. Among the possible mechanisms involved are the adipokines influence on the modulation of the expression of the receptor activator of nuclear factor kappa β ligand (RANKL), and osteoprotegerin (OPG), and increased expression of sclerostin in response to the reduction of the mechanical load. Objectives: evaluate the effect of weight loss and hormonal changes following the RYGB, on the bone metabolism. Methods: women were evaluated with obesity grades II and III in premenopausal, submitted to RYGB at the Botucatu School of Medicine University Hospital (HC-FMB), prior, three, 12 and 24 months after the procedure, as the anthropometric and laboratory data [parathyroid hormone (PTH), total alkaline phosphatase (FA total) and bone fraction (BSAP), interconnectors collagen C-terminal type I (CTX), 25-hydroxy vitamin D (25-OH Vit-D), leptin, adiponectin, RANKL, OPG and sclerostin]. Results: leptin reduction was observed [34.4 (14.7; 51.9) to 22.5 (1.9; 52.7) ng / ml] and OPG [3,6 (1,1; 11 5) to 3.4 (1.5, 6) pmol / L] after the procedure, with an increase of adiponectin [7.4 (1.7; 18.4) to 13.8 (3.0, 34, 6) ug / ml] CTX [0.2 (0.1, 2.2) to 0.6 (0.4, 6.0) ng / ml] RANKL [0.1 (0.0, 0 5) to 0.3 (0.0; 2.0) pmol / L] and sclerostin [21.7 (3.2; 75.1) to 34.8 (6.4; 80.5) pmol / L], after three months of follow-up. The BSAP also increased after 12 months of the procedure [10.1 (5.4, 18.9) to 13.9 (6.9, 30.2) mg / mL] (p <0.005). The CTX showed an inverse correlation with weight (r = -0.451), BF (r = -0.418) and FFM (r = -0.417). There was a positive correlation between CTX and total FA 12 months after RYGB and between the BSAP and PTH at 24 months after surgery (r = 0.490). This marker was negatively ...